A case for unlearning in higher education. (16th February 2023) - Posey, Allison
Abstract: The Unlearning Cycle offers a way to help educators identify some of the underlying assumptions and beliefs we bring to our pedagogical design. In a field so focused on learning, it is actually unlearning we need to focus on. This chapter shares research and strategies to trade up for new ways of teaching and designing for inclusive, rigorous learning.